Minat Siswa SMK Negeri Untuk Melanjutkan Studi Ke Perguruan Tinggi - Desti Sagita (Jurnal Pensil : Pendidikan Teknik Sipil, 2014)
The objectives of this study to to determine how much student interests SMK for continuing study into college. This study was conducted in three SMK located in East Jakarta on the second semester 2010/2011 academic year in January 2011. The research method used is descriptive and qualitative product moment correlation. The information taken from a sample of 58 students using the questionnaire Likert model that has been tested the validity and reliability. Validity is done by analyzing the grain problem.Of the 40 items tested statements contained nine items that are less qualified statement. Formula used to value reliability and acquired alpha = 0,56 indicating that the instrument has a rather low reliability. Testing the questionnaire results of the three schools tested questionnaire, the percentage of students who have an interest to continue studies into college is only 15,5%.From the percentage was only 3,5% of students who have a desire to go to college without coupled with the work, the rest are interested in college but coupled with the work. Almost all students SMKN want to be able to work right after graduation vocational school. If seen from the percentage obtained that is equal to 96,5%.The conclusion of this study is of interest that students have SMKN to continue their studies to college is very low. The students wanted to work directly after graduation vocational school. This is due to the provision of vocational students already have enough expertise in the way the work that they get from school and from the practice of fieldwork. However there are still some vocational students who have an interest to continue the study to college. This can be due to a family environment that supports students for college, both morally and materially